ABSENCE OF Trichinella spp. ANTIBODIES IN NORTHERN PERUVIAN AMAZON PECCARIES - MENAJOVSKY, Maria F. (2025)
Trichinellosis is a global parasitic food-borne disease affecting humans, domestic and wild animals. Beyond its health implications, trichinellosis also has negative economic impacts for the pork industry. However, to date, few studies have analyzed Trichinella infections in the Amazon region. This study aimed to increase the information on the circulation of Trichinella spp. in free-ranging peccaries in two areas in the Northern Peruvian Amazon. Between 2008 and 2020, local subsistence hunters collected dried blood spots on filter paper from 140 free-ranging Pecari tajacu and 93 Tayassu pecari (n= 233 total), to test for antibodies against Trichinella spp. All animals were negative in serological tests for anti-Trichinella spp. antibodies. No evidence of nematodes was also found in the histological sections of the analyzed peccary diaphragm samples (n=29). In the two study areas, free-ranging peccary populations do not show evidence of having been exposed to the parasite. This is the first survey of Trichinella spp. in wild peccaries conducted in the Amazon. Negative result studies offer key insights into trichinellosis distribution.